مستوى معرفة معاني المفردات الأدبية لدى طلبة قسم اللغة العربية والأدب الأسلامي بكلية دراسات اللغات الرئيسة, جامعة العلوم الأسلامية الماليزية : القصة القصيرة أنموزجا - Nur Farahayu Izzati Mohd Ruhani (Universiti Sains Islam Malaysia, 2024)
Vocabulary is one of the most important element to be aware by the Arabic language learner. Without it, the other language skills cannot be mastered. Through the experience of learning Arabic at the primary or secondary school, students are expected to improve their reading skills, practice and study of other Arabic subjects at higher levels. However, in university level they could not understand the texts well. The purpose of this study is to find out the level knowledge of literary vocabulary among students of Arabic Language and Islamic Literacy, Faculty of Major Language Studies at the Islamic Science University of Malaysia: Short Story as the Sample. The researcher uses quantitative method by randomly distributing test questions to 113 students from Arabic Language and Islamic Literacy Program. The researcher then analyzes using the Statistical Analysis Program (SPSS) in terms of descriptive analysis of its frequency, percentage and average value, and the correlation analysis between the average value of the level knowledge of literary vocabulary and the certificate of enrollment in the Faculty of Major Language Studies, Islamic Science University of Malaysia. The expect results of this study is the level knowledge of literary vocabulary among them is weak. The level meaning of literary vocabulary among STPM students and others certificate holders such as Matric and Diploma are weaker than STAM. Some proposals and recommendations are offered to students, lecturers, organizations from universities or schools and academicians in this area.